Dinamika Pembangunan Manusia Provinsi Jawa Barat Tahun 2020: - Dian Noviyanti (JUDICIOUS, 2021)
Development is defined as a continuous process in all fields towards a better life. Humans are an important component of development that needs to be improved. The Human Development Index (HDI) is a tool to measure the success of development. The dynamics of the HDI during 2020 need to be investigated to find out the impact of the Covid-19 pandemic on the HDI. The objectives to be achieved in this study are to determine the development of the HDI in West Java and how to group districts/cities based on variables related to HDI. The analytical method used is descriptive analysis to examine the development of HDI, while the grouping of HDI uses cluster analysis. The variables used in the cluster analysis are the components that make up the HDI including Life Expectancy (AHH), Expected Years of Schooling (HLS), Average Years of Schooling (RLS), and Adjusted Per Capita Expenditure (PPP). This research resulted in the development of HDI in 2020 which decreased both in value and in the rate of growth. The grouping of districts/cities based on cluster analysis resulted in two groups, namely the high HDI category in most cities and the low HDI category in most West Java districts.